Human Papillomavirus Infection Status of Various Laryngeal Diseases in Japan: A Comprehensive Study - Matsuzaki, Hiroumi; Makiyama, Kiyoshi; Suzuki, Hirotaka; Hirai, Ryoji; Oshima, Takeshi (Journal of voice, 2017)
The aim of our study was to clarify the human papillomavirus (HPV) infection status of various laryngeal diseases in Tokyo, Japan. This is a retrospective study. A total of 144 patients who underwent surgical resection for various laryngeal lesions were enrolled in this study. These subjects were categorized into four groups based on lesion type: non-neoplastic, 44; precancerous, 29; cancer, 35; and papilloma, 36. To determine the rate of HPV infection, laryngeal secretions and resected tissue from our study participants were examined by liquid-phase hybridization (LPH) and consensus primer-directed polymerase chain reaction (PCR). The LPH for low-risk HPV was applied to all 144 patients, and that for high-risk HPV was additionally applied to 121 of the 144 patients. The PCR was applied to 94 of the 144 patients. The LPH detected low-risk HPV-DNA in 23 patients (1 cancer and 22 papillomas) and high-risk HPV-DNA in 3 patients (1 cancer and 2 papillomas). The PCR detected HPV-6 and HPV-11 in the papilloma group, whereas it detected HPV-31 in one patient with laryngeal cancer and one patient with precancerous lesion. Both the LPH and the PCR revealed the HPV infection rate in the non-neoplastic group to be 0%. Although we found no significant difference in the HPV-DNA positive rates of laryngeal cancer and precancerous lesions in the non-neoplastic group, the positive rates were significantly smaller in this group than in the papilloma group. In the Tokyo area, HPV had little or no association with laryngeal cancer, precancerous lesions, and non-neoplastic lesions in the larynx.